Effect of different spacings and nitrogen levels on growth and yield of cauliflower (Brassica oleracea var. botrytis L.) under north Gujarat condition - Jat, M.L.; Patel, M.M.; Bana, M.L. (Annals of Agricultural Research, 2016)
A field experiment was conducted during rabi season of 2010-11 at the Horticultural Instructional Farm, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar to study the effect of different spacing and nitrogen levels on growth and yield of cauliflower (Brassica oleracea Var. botrytis L.) under North Gujarat conditions. The results of experiment revealed that the spacings significantly increased maximum plant height (22.6 cm and 33.7 cm at 30 days after transplanting (DATP) and at harvest, respectively), number of leaves per plant (12.3 and 27.9 at 30 DATP and harvest, respectively), diameter of curd (14.6 cm) were observed in 45 cm X 30 cm spacing, and the highest average weight of curd (831.4 g) was recorded under treatment 45 cm X 45 cm spacing. Regarding nitrogen levels, crop fertilized with 200 kg ha-1 recorded the highest plant height (22.5 cm and 33.4 cm at 30 DATP and at harvest, respectively), number of leaves per plant (12.1 and 25.9 at 30 DATP and harvest, respectively), diameter of curd (14.83 cm), average weight of curd (628.06 g).